2022
DOI: 10.3390/metabo12080746
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Composition and Biochemical Parameters with Antioxidant Status in a Healthy Cohort of Postmenopausal Women

Abstract: Background and aims: An adequate prooxidant–antioxidant balance—which may be influenced by body composition and biochemical status—is essential to maintain human health, especially in circumstances under which the antioxidant defense decreases, such as menopause. The present study aimed to examine the relationship between body composition and biochemical parameters with antioxidant status in a healthy cohort of postmenopausal women. Methods: This cross-sectional study was carried out in a cohort of 78 postmeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…What is more, obtained clinical results in the healthy aged population showed discrepancies. Kozakiewicz and colleagues described a decrease in crucial activity of antioxidative enzymes with the simultaneous intensity of lipids peroxidation [52], while Vázquez-Lorente et al argued that in a postmenopausal population, antioxidant parameter values showed no changes with aging [53], but the activity of total antioxidant capacity were affected by body composition and directly related to plasma proteins [54]. Differences in the results of the researchers may be explained by the selection of different populations, age ranges or genders, co-morbidities or even no disease existence in investigated age groups.…”
Section: Theories Of Aging Oxidative Stress and Inflammagingmentioning
confidence: 99%
“…What is more, obtained clinical results in the healthy aged population showed discrepancies. Kozakiewicz and colleagues described a decrease in crucial activity of antioxidative enzymes with the simultaneous intensity of lipids peroxidation [52], while Vázquez-Lorente et al argued that in a postmenopausal population, antioxidant parameter values showed no changes with aging [53], but the activity of total antioxidant capacity were affected by body composition and directly related to plasma proteins [54]. Differences in the results of the researchers may be explained by the selection of different populations, age ranges or genders, co-morbidities or even no disease existence in investigated age groups.…”
Section: Theories Of Aging Oxidative Stress and Inflammagingmentioning
confidence: 99%